RESEARCH ON THE RECOVERY OF SOME AGRICULTURAL WASTE FOR THE MANUFACTURE OF COMPOSITE MATERIALS WITH CLAY MATRICES - ELENA SURDU; CLAUDIA-DANA FARCAȘ-FLAMAROPOL; PETRU CÂRDEI; ION DURBACĂ; NICOLETA SPOREA (Journal of Engineering Studies and Research)
The article describes the results of the research carried out for the systemic description of the manufacturing technological processes of composite materials with clay matrix and insert from agricultural waste. The objectives of these researches include the valorization of agricultural waste and cheap and abundant resources to obtain composite materials usable in civil constructions or various rural developments, with properties superior to existing ones, for example adobe or clay bricks. The article describes the materials used, the technology of obtaining, the dependence between the output parameters and the input and control parameters.